A 27–31 ​GHz 6-bit phase shifter with low phase error/gain variation in 65 ​nm CMOS. (October 2020) - Chen, Zipeng; Li, An'an; Jia, Haikun; Chi, Baoyong
Abstract: This paper presents a Ka-band 6-bit phase shifter with low phase error, low gain variation and 27–31 ​GHz bandwidth implemented in 65 ​nm CMOS. The phase shifter consists of a reflective-type phase shifter (RTPS) and a 0°/180° switcher. Benefiting from the addition of the switcher and the optimization of RTPS circuits, higher Q of the reflective load is obtained to improve the phase shifting performance. Measured results of the proposed phase shifter show 5.625° (6-bit) phase resolution, 1.64° in-band RMS phase error, 7.6 ​dB gain and 0.59 ​dB in-band RMS gain variation across the 4 ​GHz bandwidth, which are outstanding compared with the state-of-the-art works. The chip has 0.56 ​mm 2 area and 24 ​mW power consumption.